2023
DOI: 10.7759/cureus.34155
|View full text |Cite
|
Sign up to set email alerts
|

An Immunohistochemical Study on Ki-67 Expression in Squamous Cell Carcinomas of Cervix With Clinicopathological Correlation

Abstract: BackgroundCervical carcinoma is one of the most prevalent cancers affecting women worldwide. Studies on Ki-67 expression in cervical lesions had focused mainly on the intraepithelial lesions of the cervix and not much on invasive carcinomas. The few studies published so far on Ki-67 expression in invasive cervical carcinomas have shown inconsistent results on the association of Ki-67 with various clinicopathological prognostic factors. Aims and objectivesTo assess Ki-67 expression in cervical carcinomas and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…In addition, despite the lack of significant association between Ki-67 expression and clinicopathologic features in patients with DLBCL observed in this study, it should be noted that such associations have been reported in various malignancies, including DLBCL. [51][52][53] For instance, in a study conducted by Hashmi et al, patients with non-GCB subtype demonstrated a significantly higher Ki67 index when compared with those with the GCB subtype of DLBCL. Additionally, a positive association was found between c-MYC expression and a higher Ki-67 index.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, despite the lack of significant association between Ki-67 expression and clinicopathologic features in patients with DLBCL observed in this study, it should be noted that such associations have been reported in various malignancies, including DLBCL. [51][52][53] For instance, in a study conducted by Hashmi et al, patients with non-GCB subtype demonstrated a significantly higher Ki67 index when compared with those with the GCB subtype of DLBCL. Additionally, a positive association was found between c-MYC expression and a higher Ki-67 index.…”
Section: Discussionmentioning
confidence: 99%
“…Ki67 was scored as positive when brown staining was present in the nucleus at any intensity. The positive staining was further categorized in three-grade scale in a semi-quantitative manner as: Score 1: 10–30% stained cells (Low proliferation); Score2: 30–50% stained cells (moderate proliferation); Score3: > 50% (high proliferation) 70 .…”
Section: Methodsmentioning
confidence: 99%
“… 6 Ki-67 is related to the cell cycle and mitosis and is commonly used in clinical settings to measure cellular proliferation. 7 Ki-67 expression measured through immunohistochemical (IHC) staining has been identified as a biomarker to predict the prognosis of different cancer types, such as breast cancer, 8 multiple myeloma, 9 cervical cancer, 10 diffuse malignant peritoneal mesothelioma 11 and oral squamous cell carcinoma. 12 Many studies have examined the role of Ki-67 in predicting ESCC prognosis, but no consistent findings have been obtained.…”
Section: Introductionmentioning
confidence: 99%